Karakterisasi Protein Lernaea Cyprinacea Dengan Metode Elektroforesis SDS-PAGE [Characterization Of Protein Lernaea cyprinacea By Using SDS-PAGE Electrophoresis Method] - Gunanti Mahasri; Ulia Fajriah; Sri Subekti (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
Abstract One of the diseases that often attack are fish is parasitic disease caused by Lernaea cyprinacea, called Lernaeosis. This ectoparasites could be detected on skin, gill, eyes, fin or inside of mouth and nostril of fishes. The aim of the study was to know the character is tic of L.cyprinacea protein based on molecular weight using SDS-PAGE. The results of this study were expected as Lernaeosis vaccine candidate. The experiment used SDS-PAGE with 12% separating gel, 3% stacking gel, voltage 110 volts 28 A and gel staining using coomassie blue. The result showed that, there were eight protein bands with molecular weight 82.3, 73.3, 66.6, 60.5, 54.9, 27.5, 23.1 and 19.8 kDa. Among them, the bands with molecular weight 27.5, 23.1 and 19.8 kDa were thicker and clearer than the others.